Combination of a solar collector and thermoelectric cooling modules in a humidification–dehumidification desalination system-experimental investigation with energy, exergy, exergoeconomic and environmental analysis. (1st December 2020) - Omidi, Bagher; Rahbar, Nader; Kargarsharifabad, Hadi; Rashidi, Saman
Highlights: A new water desalination system using hybrid solar collector with two working fluids. Eight thermoelectric cooling modules used to condense water vapor. The productivity increases about 13% by using the thermoelectric cooling. Daily productivity increases about 55% with increasing the flow rate of saline water. Using 3-E analysis to show CO2 mitigation and system economic potentials. Abstract: In this study, a novel humidification–dehumidification desalination (HDD) system, consisting of a hybrid solar collector with two working fluids, air and ethylene glycol, is designed and tested under climatic condition of Tehran, Iran. In this design, air passes above the absorber plate, while ethylene glycol flows through the copper tubes located on the absorber plate. The dehumidification system is also equipped with thermoelectric cooling modules. The effects of different parameters including collector outlet air velocity, volumetric flow rates of ethylene glycol and saline water and the effect of thermoelectric cooling on the performance and exergy of the system have been investigated. The experimental results showed that the water production improves by 8% with increasing the collector outlet air velocity from 2.2 to 3 m/s, while it reduces by 17% when increasing the collector outlet air velocity in the range of 3 to 4.2 m/s. In addition, the daily productivity increases about 44% by increasing the volumetric flow rate of ethylene glycol in the collector in the range of 0.83 L/min to 2.24 L/min. Moreover, the daily productivity of the system improves about 55% by increasing the volumetric flow rate of saline water from 0.66 L/min to 3 L/min. Furthermore, the productivity improves about 4% as the distance between the glass cover and the absorber plate decreases from 27.25 mm to 14.75 mm. The results also show that the productivity increases about 13% by using the thermoelectric cooling system. Finally, the maximum hourly exergy efficiency and maximum daily exergy efficiency were measured as 12.75% and 8.78%, respectively. Economic analysis shows that the estimated cost of water production is 0.097 $/lit/m 2 which is comparable with the other devices reported in the literature. Finally, the exergoeconomic and environmental analysis are analyzed and discussed to show CO2 mitigation and economic potential of the system.